Review of calculation, payment and reporting Swallow bird nest tax in Makassar - Muhammad Ma'ruf; Imron Burhan; Ilham Ilham (Income Journal: Accounting, Management and Economic Research, 2022)
Makassar City Regional Regulation No. 3 of 2010 on Local tax explained that the bird nest tax is a tax on extraction and exploitation activities bird nest. Swallow bird's nest production potential of Indonesia reached 400,000 kg / year, then the government must undertake the improvement in the financial area is managed effectively and efficiently. Tax collection system used in performing tax collection of bird's nest is a self-assessment system. The study aims to determine the calculation, payment, and Tax Reporting Swallow's Nest in Makassar. This study is a qualitative research. Informants in this study is the taxpayer Swallow's Nest in Makassar with the determination of purposive sampling technique. Data analysis technique used is descriptive method with qualitative analysis. The results of this study indicate that the taxpayer Swallow's Nest in Makassar has made the calculation, payment, and reporting in accordance with the Regional paraturan Makassar No. 3 of 2010 on Local tax,